Butea Monosperma’s Phytochemical Properties and its Antibacterial, Antioxidant, and Hypoglycemic Effects - Khan, Zaafran; Zeb, Anum; Sheikh, Fatima Akbar (Indus Journal of Bioscience Research, 2025)
The medicinal traditions of Butea monosperma (flame of the forest) are supported by its diverse phytochemical profile and multiple biological activities. This study investigates the antibacterial, antioxidant, and hypoglycemic properties of ethanol, methanol, ethyl acetate, and chloroform extracts from the leaves, flowers, bark, and seeds of the plant. Phytochemical screening revealed the presence of alkaloids, tannins, flavonoids, sterols, and glycosides, with methanolic extracts showing the highest abundance. Antibacterial activity, assessed via the disk diffusion method, showed significant inhibition of both Gram-positive and Gram-negative bacteria, with methanolic leaf extract demonstrating the largest inhibition zones against Pseudomonas aeruginosa and Staphylococcus aureus. Antioxidant activity, evaluated using the DPPH free radical scavenging assay, was most potent in methanolic leaf and flower extracts. Furthermore, methanolic flower extract exhibited a pronounced hypoglycemic effect in alloxan-induced diabetic rabbits, reducing blood glucose by 44% over three weeks and stabilizing body weight. These findings reinforce the therapeutic potential of Butea monosperma as a natural source of antibacterial, antioxidant, and hypoglycemic agents, validating its use in traditional medicine and highlighting its promise for pharmaceutical applications.